If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18(x * x) = 12 + 15x Multiply x * x 18(x2) = 12 + 15x Solving 18x2 = 12 + 15x Solving for variable 'x'. Reorder the terms: -12 + -15x + 18x2 = 12 + 15x + -12 + -15x Reorder the terms: -12 + -15x + 18x2 = 12 + -12 + 15x + -15x Combine like terms: 12 + -12 = 0 -12 + -15x + 18x2 = 0 + 15x + -15x -12 + -15x + 18x2 = 15x + -15x Combine like terms: 15x + -15x = 0 -12 + -15x + 18x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-4 + -5x + 6x2) = 0 Factor a trinomial. 3((-1 + -2x)(4 + -3x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5Subproblem 2
Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333Solution
x = {-0.5, 1.333333333}
| 1-(-x-4)=2x | | -50=-7x-5(-2x+4) | | T-3t+6-2= | | 12+w=16 | | 1234567890-9856219= | | 2(c-7)+3(x-1)=4x+3 | | 16(x+3)=4(4x+1)+44 | | X+7+23x=23 | | -2x-4(-5x+18)=144 | | 1-(11x+3)=5 | | T(15-5t)=0 | | 0.5(x-3)=7 | | -8(t-2)-3(3t+1)=-4 | | 40*3= | | -25=4x+5 | | 19=-11+2x | | 2n+14-4n=26 | | 56x^2=79x-9 | | 3y+5=2x+1 | | 5x-3=3+2x | | 13-9x=-50 | | y+3=-11 | | 12=7x+25 | | 12x+124=-32 | | 79=7x+12 | | 120-11x=-34 | | x+4-5x=3 | | 0.20s+0.32=520s | | (8y-7x)(8y+7x)= | | 0.18M+16=40.54M | | 12-7x=-6 | | -9-5x=-54 |